Persepsi Pengggunaan E-wallet OVO pada Generasi Z di Masa Pandemi Covid-19 - Annisa Retno Utami (Yayasan Literasi Sains Indonesia, 2022)
The development of digital technology has made changes in making transactions, one of these developments with the emergence of various kinds of e-wallets, namely OVO. OVO as one of the e-wallets that are widely used by Generation Z. In this study, it aims to determine the perception of the use of OVO e-wallets in Generation Z during the Covid-19 pandemic. The sample in the study used was 100 respondents with a susceptibility age of 18-25 years. The distribution of questionnaires using a google form given to respondents who use OVO in making transactions during the Covid-19 pandemic. Data analysis method using descriptive analysis. Descriptive analysis is used to describe the results of research on consumer perception variables using OVO during the Covid-19 pandemic. The results of this study showed that the perception of ease in making transactions had the highest value with a result of 93 and the lowest result in inni's research on trustworthy security security of 63. The perception measurement in this study was seen from three perceptions, namely benefits, convenience and safety and risk.